1998
DOI: 10.1007/s002770050405
|View full text |Cite
|
Sign up to set email alerts
|

Iron status in 268 Danish women aged 18-30 years: influence of menstruation, contraceptive method, and iron supplementation

Abstract: The aim of the present study was to evaluate the influence of menstruation, method of contraception, and iron supplementation on iron status in young Danish women, and to assess whether iron deficiency could be predicted from the pattern of menstruation. Iron status was examined by measuring serum (S-) ferritin and hemoglobin (Hb) in 268 randomly selected, healthy, menstruating, nonpregnant Danish women aged 18-30 years. Iron deficiency (S-ferritin <16 microg/l) was observed in 9.7%, of the women, iron deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 22 publications
4
85
1
7
Order By: Relevance
“…We found that women without contraception had a higher elimination of iron, which led to steady-state concentrations of iron lower by about 20% compared to women using contraception. It has been shown that contraception regulates the abundance of menses (34) and therefore limits iron loss (35), which can explain this finding. Iron concentrations at steady-state were also affected by body size, as we found that iron absorption decreased when the body mass index increased.…”
Section: Discussionmentioning
confidence: 82%
“…We found that women without contraception had a higher elimination of iron, which led to steady-state concentrations of iron lower by about 20% compared to women using contraception. It has been shown that contraception regulates the abundance of menses (34) and therefore limits iron loss (35), which can explain this finding. Iron concentrations at steady-state were also affected by body size, as we found that iron absorption decreased when the body mass index increased.…”
Section: Discussionmentioning
confidence: 82%
“…Due to the regular blood and iron losses at their menstrual periods, women of reproductive age a priori face a difficult situation concerning their iron balance. The amount of iron lost by menstruation varies from woman to woman, but is quite constant in the individual women [24]. Natural mechanisms in women have not compensated for these iron losses.…”
Section: Women Of Reproductive Agementioning
confidence: 99%
“…The lowest prevalence ~25% is found in Europe and the Americas, whereas South-East Asia and Africa present high prevalences of 48% and 57%, respectively [3]. In Denmark, pregnant women who do not take iron supplements have a prevalence of anemia of ~25% [24]; in contrast, the prevalence of anemia in women taking 40 mg ferrous iron daily is below 5% [25].…”
Section: Pregnant Womenmentioning
confidence: 99%
“…[13][14][15] It is projected that India has the utmost prevalence of anemia, i.e., 57-96.2%, among the South Asian countries. [16][17][18] To combat the high prevalence of IDA several government programs and state level schemes were rolled out in various states of India.…”
Section: Past Efforts and Current Scenariomentioning
confidence: 99%